Teamwork as a Self-Disciplining Device - Matthias Fahn; Hendrik Hakenes (Center for Economic Studies and ifo Institute (CESifo), 2014)
We show that team formation can serve as an implicit commitment device to overcome problems of self-control. In a situation where individuals have present-biased preferences, any effort that is costly today but rewarded at some later point in time is too low from the perspective of an individual's long-run self. If agents interact repeatedly and can monitor each other, a relational contract involving teamwork can help to improve an agent's performance. The mutual promise to work harder is credible because the team breaks up after an agent has not kept this promise - which leads to individual (under-) production in the future and reduces an agent's future utility. This holds even though the standard free-rider problem is present and teamwork renders no technological benefits. Moreover, we show that even if teamwork does render technological benefits, the performance of a team of present-biased agents can actually be better than the performance of a team of time-consistent agents.
Keywords: L22; L23; 330; procrastination; hyperbolic discounting; self-control problems; teamwork; relational contracts